Sustainable agriculture: women and pesticides (2000)
All over the World, women are the primary producers of food for their families and extended communities. In sub-Saharan Africa, more than half of the farm labour force consists of women yet they have little or no knowledge of the hazards of pesticides that are often applied at the various stages of crop production. Numerous studies on pesticides related poisoning have been reported on many male farmers but relatively fewer studies have been conducted on women because of their subordinate position in the society. At the superficial level, it is believed that women do not spray pesticides, but they are exposed lo pesticides during the washing of sprayers and clothing. and the processing and consumption of treated crops. Women are particularly vulnerable because of the aggravating conditions like poverty, ignorance, malnutrition that are caused by their subordinate rotes In the society. Pesticides are known to cause breast cancer, infertilely, spontaneous abortion, still - birth and birth defects in exposed women. To achieve sustainable agriculture, it is therefore important that women indigenous knowledge and skills are used for the development of less hazardous crop production practices.